Pipistrellus nathusii - Karl F. Koopman (Smithsonian Institution Press, 1993)
Pipistrellus nathusii (Keyserling and Blasius, 1839). Arch. Naturgesch., 5(1):320. TYPE LOCALITY: Germany, Berlin. DISTRIBUTION: W Europe to Urals and Caucasus, and W Asia Minor; S England. SYNONYMS: unicolor. COMMENTS: Subgenus Pipistrelli. Published as part of Karl F. Koopman, 1993, Order Chiroptera, pp. 137-241 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 222, DOI: 10.5281/zenodo.7353060